'lym wgybwrym: 'lylwt kn ׳ nywt šnmṣ'w b' wgryt / Gods and Heroes: Canaanite Epics from Ugarit - Amir, David (1987)
including some epics never before published in Hebrew; in Hebrew with English table of contents